LAWS, CHALLENGES, SOLUTIONS RELATED TO WORKPLACE SEXUAL HARASSMENT IN INDIA - Roselin.V.N; Rao, B. Someswara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Despite legislative measures in India through the Sexual Harassment of Women at Workplace (Prevention, Prohibition and Redressal) Act, 2013 (PoSH Act), workplace sexual harassment continues to be a cause for concern. This article takes a closer look at how common sexual harassment is in the workplace in India, whether existing laws protect women, and if they do, how the lack of implementation renders them akin to scraps of paper. Although the PoSH Act mandates the setting of Internal Committees (ICs) to provide redressal mechanisms for complaints of sexual harassment at the workplace, ignorance, fear of retaliation and the prevailing stigma of sexual harassment discourages women from reporting incidents. Furthermore, many organizations operate outside the law, making enforcement nearly impossible. However, it is not just regulations, but also workplace culture where the accountability for harassment is born. It is essential that organizations take preventive actions, gender-sensitization training, anti-harassment policies, and anonymous reporting channels. Leadership is of utmost importance regarding creating a safe and inclusive workplace. It also describes landmark cases and legal precedents that wanted India to handle workplace harassment. Demand for policy changes, the gap between what should be happening under the law and what is being enforced and holding corporations accountable. By tackling these issues and nurturing a spirit of non-tolerance, India can head towards safer and fairer workplaces for everyone.